Case Report: Extracorporeal Membrane Oxgenation for Rapidly Progressive Interstitial Lung Disease Associated With Clinically Amyopathic Dermatomyositis in a Post-partum Woman - Gu, Qiao; Diao, MengYuan; Hu, Wei; Huang, Man; Zhu, Ying (Frontiers in Medicine, 2021)
Background: Clinically amyopathic dermatomyositis (CADM) who present with rapid progressive interstitial lung disease (RP-ILD) is rare. Here, we present a case of a postpartum female with CADM complicated by severe RP-ILD managed with venovenous extracorporeal membrane oxygenation (V-V ECMO). Case Summary: A 36-year-old woman was referred to a local hospital with cough and fever. She had a history of facial erythema and cough since an induction of labor for a stillborn fetus 2 months ago. Her status developed into RP-ILD with mediastinal emphysema and subcutaneous emphysema after admission, and V-V ECMO was initiated. After several failed attempts to wean the patient from ECMO, a decision was made to place the patient on the lung transplant waitlist. She underwent a double lung transplant on ECMO day 31 and received tacrolimus as an immunosuppressive regimen. The patient presented with positive anti-MDA5 and anti-Ro-52 antibodies and a high ferritin level, all of which indicated the presence of clinically amyopathic dermatomyositis (CADM). The patient was weaned from ECMO at 3 days after transplantation, but the patient's state of consciousness deteriorated, and head CT was considered for posterior reversible encephalopathy syndrome (PRES). After the temporary cessation of calcineurin inhibitors and a dosage reduction, the patient’s state of consciousness returned to normal. Because of another disturbance of consciousness, the patient declined further treatment and was discharged 14 days after transplantation. Conclusion: Early recognition of CADM can effectively improve patients’ prognosis. ECMO should be considered as a supportive therapy in patients in acute respiratory failure secondary to RP-ILD.